Imagination of Tehran: Study of "Mindscape of the City" through 1340s and 1350s Iranian Cinema - Azam Ravadrad; Baharak Mahmoodi (Taḥqīqāt-i Farhangī-i Īrān)
This paper aims to study the imagination of Tehran through 1340s and 1350s Iranian cinema and the main question is that what kind of representation on city was fueled by cinema. This study was conducted based on analysis of four impressive films in these two decades. Two of them are popular movies (Ganje Gharoon and Khater Khah) and the two other (Khesht-o Ayeni and Ragbar) are related to avantgarde cinema. Although they are different in presenting the city in some aspects, the results reveal that both approaches emphasise on the negative aspects of the city and expose latent contradictions in the extreme way.